EFFECTIVE STRATEGIES FOR TEACHING MUSIC THEORY THROUGH INTERACTIVE LESSONS - Jalilov Shokir Isomiddinovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores strategies for teaching music theory effectively through interactive lessons. It examines pedagogical approaches, digital tools, and classroom techniques that enhance student engagement, creativity, and comprehension. The paper emphasizes the use of interactive platforms, simulations, multimedia resources, and collaborative activities to create student-centered learning environments. The role of interactivity in improving theoretical understanding, auditory skills, and analytical abilities is also discussed.